2020
DOI: 10.1002/iub.2240
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of microRNA‐197 expression suppresses oncogenicity in fibrosarcoma through negative regulation of RAN

Abstract: MicroRNAs (miRNAs) act as crucial regulators of biological pathways/processes by reinforcing transcriptional programs and moderating transcripts. Emerging evidences have shown the involvement of dysregulated miRNAs in pathophysiology of human diseases including several cancer types. Recently, miR‐197‐3p has been reported to play different roles in different cancers; however, its role in fibrosarcoma, a highly aggressive and malignant soft tissue sarcoma originated from the mesenchymal tissues, has not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Jain et al . reported that hsa-miR-197-3p regulates fibrosarcoma carcinogenicity by targeting RAN [ 74 ]. It will be interesting to understand the unknown molecular mechanism behind the role of the RAN in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Jain et al . reported that hsa-miR-197-3p regulates fibrosarcoma carcinogenicity by targeting RAN [ 74 ]. It will be interesting to understand the unknown molecular mechanism behind the role of the RAN in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study manifested that the soluble pattern recognition receptor long-pentraxin 3 (PTX3) may act as an oncosuppressor, functioning as an antagonist of the fibroblast growth factor/fibroblast growth factor receptor (FGF/FGFR) system to inhibit FGF-dependent tumor growth. 25 Jain et al 26 found that miR-197-3p can significantly inhibit the viability, colony formation, migration as well as triggers G2/M phase cell cycle arrest of fibrosarcoma cells. For the recurrent fibrosarcoma with high expression of vascular endothelial growth factor (VEGF), apatinib could effectively reduce the risk of disease progression in patient with recurrent fibrosarcoma, which highly expressed vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study manifested that the soluble pattern recognition receptor long-pentraxin 3 (PTX3) may acts as an oncosuppressor, functioning as an antagonist of the broblast growth factor/ broblast growth factor receptor (FGF/FGFR) system to inhibit FGF-dependent tumor growth [16]. Jain et al [25] found that miR-197-3p can signi cantly inhibit the viability, colony formation, migration as well as triggers G2 / M phase cell cycle arrest of brosarcoma cells [17]. For the recurrent brosarcoma with high expression of vascular endothelial growth factor (VEGF), apatinib could effectively reduce the risk of disease progression in patient with recurrent brosarcoma, which highly expressed vascular endothelial growth factor (VEGF) [18].…”
Section: Discussionmentioning
confidence: 99%